2018
DOI: 10.1186/s40352-018-0081-6
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus screening and treatment in Irish prisons from a governor and prison officer perspective - a qualitative exploration

Abstract: BackgroundPrisons are a key location to access Hepatitis C Virus (HCV) infected people who inject drugs (PWID). Prison health care structures are complex and optimising health care delivery to this high need, marginalised and underserved population remains challenging. Despite international guidelines recommending that prisons are a priority location for HCV screening and treatment levels of prisoner engagement in HCV care remain low. Competing priorities between security and healthcare is a key feature of pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 57 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Similar to other jurisdiction, Ireland struggles to increase rates of HCV screening and treatment in prisoners [ 12 , 15 , 16 ]. Barriers identified include: lack of knowledge, historical requirement to have a liver biopsy, the requirement to go to hospital, concerns regarding confidentiality, stigma experienced and inconsistent and delayed access to prison health services [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other jurisdiction, Ireland struggles to increase rates of HCV screening and treatment in prisoners [ 12 , 15 , 16 ]. Barriers identified include: lack of knowledge, historical requirement to have a liver biopsy, the requirement to go to hospital, concerns regarding confidentiality, stigma experienced and inconsistent and delayed access to prison health services [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies have reported on the lived experience of HCV infected PWID in the community[2527]. Previous studies have reported on barriers, enablers and motivators to prisoners’ engagement with HCV care[2830]. To our knowledge this is the first study to report on HCV infected prisoners’ experience of the entire HCV continuum of care, from infection to cure, both in the community and prison.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is significantly higher than a pooled prevalence in general population (2%), among pregnant women 1.83% and blood donors 0.819% [ 18 , 21 , 22 ]. Prisoners have a high risk of contracting HCV, thus regular health checks and the detection of infected individuals and identifying associated factors are crucial to preventing the disease and lowering the risk of transmission both within and outside of prisons [ 50 ].…”
Section: Discussionmentioning
confidence: 99%